S = u + a (n- 1/2)

**Answer:**

Yes

**See the explanation given by Vimal Raj**

If we notice the derivation of this formula

let t1=x and t2=y (for my easiness)

S(y)=uy + 1/2 ay^2----------(1)

S(x)=ux + 1/2 ax^2-----------(2)

sub (2) from (1)

S(y)-S(x)=uy + 1/2 ay^2 - ux - 1/2 ax^2

S(y)-S(x)=u(y-x)+a/2(y^2-x^2)

here we know y-x =1 s ,then

Sn = u (1s) + a/2(y+x)(y-x)

Sn =u(1s) + a/2(y+x)(1s)

Dimension of Sn must be equal to u(1s)

u=LT^1

THEN Sn=[LT^1][T]=[L]

(Also Visit https://www.facebook.com/groups/askphysics/ for obtaining help from the Facebook group members)

## No comments:

## Post a Comment

Do not spam. Spammers will be banned from this site